8-Anilino-1-naphthalenesulfonate-Conjugated Carbon-Coated Ferrite Nanodots for Fluoromagnetic Imaging, Smart Drug Delivery, and Biomolecular Sensing - Anbazhagan Thirumalai; Koyeli Girigoswami; Alex Daniel Prabhu; Pazhani Durgadevi; Venkatakrishnan Kiran; Agnishwar Girigoswami (Pharmaceutics)
Background: Superparamagnetic properties and excitation independence have been incorporated into carbon-decorated manganese ferrite nanodots (MnFe@C) to introduce an economical and safer multimodal agent for use in both T1-T2 MRI and fluorescence-based imaging to replace the conventional highly toxic heavy metal contrast agents. Methods: The surface conjugation of 8-anilino-1-naphthalenesulfonate (ANS) to MnFe@C nanodots (ANS-MnFe@C) enhances both longitudinal and transverse MRI relaxation, improves fluorescence for optical imaging, and increases protein detection sensitivity, showing higher multimodal efficacy in terms of molar relaxivity, radiant efficiencies, and fluorescence sensitivity compared to MnFe@C. Results: The band gap energy was determined using Tauc’s equation to be 3.32 eV, while a 72% quantum yield demonstrated that ANS-MnFe@C was highly fluorescent, with the linear range and association constant calculated using the Stern–Volmer relation. The synthesized ANS-MnFe@C demonstrated excellent selectivity and sensitivity for bovine serum albumin (BSA), with a nanomolar detection limit of 367.09 nM and a broad linear range from 0.015 to 0.225 mM. Conclusions: In conclusion, ANS-MnFe@C holds ease of fabrication, good biocompatibility, as assessed in A375 cells, and an effective pH-sensitive doxorubicin release profile to establish anticancer activity in lung cancer cell line (A549), highlighting its potential as an affordable therapeutic agent for multimodal imaging, drug delivery, and protein sensing.